Histoarchitecture and Histochemical Studies on the Abomasum of Sheep (Ovis aries) - Poonia, Amit; Kumar, Pawan (Indian Journal of Veterinary Anatomy, 2018)
The present study was conducted on abomasum of ten young sheep, aged 6-9 months of local mixed breed. The abomasal mucosa lined by simple columnar epithelium was divided into cardiac, fundic and pyloric regions. The cardiac gland region was the smallest and confined to omaso-abomasal orifice and its glands were simple, branched, tubular and coiled type. In the fundic gland region, the mucosa showed elevations called gastric areas which were separated from each other by gastric pits. The fundic glands were simple branched, tubular and coiled type and had varying number of mucous neck, chief, parietal and endocrine cells. The PAS reactivity was comparatively more towards the base of gastric pits. The surface epithelial cells were strongly positive for the acidic and neutral mucopolysaccharides with the predominance of the later. The surface epithelial cells werestrongly PAS positive in pyloric region showing the presence of glycogen, acidic and neutral mucopolysaccharides.